Forage production and productive performance of Nellore heifers in agrosilvopastoral systems (Research, Society and Development, 2020)
Agrosilvopastoral system is a type of production that involves the soil-forage-animal interface, both of which are benefited by the system. Hence, the present study evaluated the effects of agrosilvopastoral system on the quantitative and qualitative characteristics from pasture, and the animal performance during the feeding period of Nellore heifers. The treatments included: Soil-forage-animal – 357 eucalyptus trees per hectare (LFA14x2m); Soil-forage-animal – 227 eucalyptus trees per hectare (LFA22x2m); and Soil-animal – Five native trees remaining per hectare (CON). The forage used was Brachiaria brizantha cv. BRS Piatã and having as trees planted the Eucalyptus urograndis clones H 13. Treatment effects (P